Intra and interpersonal abilities as well as English oral communicative skills that call centers require candidates to have to be hired and employees to stay at work longer than short-time stayers, in the city of San Salvador and year 2015. - Melgar Orellana, Álvaro Daniel
There is evidence that the industry of telecommunication in El Salvador has been growing considerably. According to La Prensa Gráfica, this industry has been growing at a rate of 29% every year since 2005. Therefore it has become a great source of employment for English speakers. PROESA (Agencia de Promoción de Exportaciones e Inversiones de El Salvador) stated that call centers employ more than 12,000 people permanently. Nevertheless, the curious fact is that many of the applicants of a position at a call center are currently studying or have studied to become English teachers. Based on a dissertation publicized by Ruth Elizabeth Gamero and Irma Dínora Pérez entitled as “ Real Job Market in the Metropolitan Area of San Salvador for professionals graduated in Licenciatura en el Idioma Inglés Opción: Enseñanza. Main campus of the University of El Salvador, 2007”, out of 100 students surveyed from such a major less than half said they wanted to work as teachers. And taking the University of El Salvador as a reference, the Foreign Languages Department offers only a major in the teaching of English. This does not match with the labor market demand that goes beyond hiring only people trained for teaching English. Consequently, the need of offering students a major in the telecommunication area has strongly emerged, requiring local universities to adjust to these new changes. This disparity between what universities are offering and what the labor market is demanding has turned into the leading cause of this work. Hence, the intention is also to seek alternatives which could help the University of El Salvador update or incorporate majors linked to the current labor needs